Application of Expert System for Diagnosing Gastric Disease Android Based with Certainty Factor Method - Avicienna Adhi Narendro Purnomo; Septi Andryana; Agus Iskandar (Institute of Computer Science (IOCS), 2020)
Expert systems are computer programs that mimic reasoning an expert with expertise in an area of knowledge, the present study, how to diagnose diseases of the stomach to build an expert system that can analyze the symptoms of the disease into a decision, the method Cerataity Factor as a method for calculating confidence in the value provided by the patient's symptoms. The purpose of this study is to provide convenience to the public for mediagnosa a disease of the stomach suffered and gave information about diseases of the stomach and provide solutions when terjankit gastric diseases. Of the many diseases in carefully then there are various symptoms sample to meet the needs of the weights that have been defined by experts.